Bradykinin-Mediated Angioedema: An Update of the Genetic Causes and the Impact of Genomics - Marcelino-Rodriguez, Itahisa; Callero, Ariel; Mendoza-Alvarez, Alejandro; Perez-Rodriguez, Eva; Barrios-Recio, Javier; Garcia-Robaina, Jose C.; Flores, Carlos (Frontiers in Genetics, 2019)
Recurrent episodes of bradykinin-mediated angioedema (Bk-AE) can associate with hereditary or acquired conditions, the latter developing most commonly secondary to a pharmacological treatment. Despite the successful advances in genomics, leading to a discovery of a large number of causal and susceptibility genes for many rare and complex diseases, their translation to the study of the genetic etiology of Bk-AE has barely occurred. As a consequence, the genetics of Bk-AE subtypes remain poorly understood, obstructing the development of precision medicine strategies. This review summarizes the limited evidence available from the few and underpowered genetic studies performed to date on the acquired subtypes, almost exclusively focusing on Bk-AE secondary to the angiotensin-converting enzyme inhibitor treatment, and the recent subdivision of hereditary forms as a consequence of applying holistic next-generation sequencing technologies (NGS) to undiagnosed patients. Finally, based on the increase in the diagnostic yield compared to classic methods and the drastic reductions in their costs, arguments favoring the use of holistic NGS approaches as first-tier genetic tests are presented as a promise to reduce the diagnostic odyssey of patients with suspected hereditary forms of Bk-AE.